Determinants of influenza and pneumococcal vaccine uptake among preschool children in Singapore. - Marina Zahari; Vittoria Offeddu; Gavin J D Smith; Clarence C Tam (PLoS ONE, 2023)
Young children are at increased risk of severe illness from influenza and pneumococcal infections. The World Health Organization (WHO) recommends vaccination with influenza and pneumococcal conjugate vaccine (PCV). However, in Singapore, vaccine uptake remains suboptimal relative to other routine childhood immunisations. Limited information exists regarding determinants of influenza and pneumococcal vaccine uptake in children. We estimated vaccine uptake and investigated factors associated with influenza and pneumococcal vaccination status by age group using data from a cohort study on acute respiratory infections in children attending preschools in Singapore. We recruited children aged two to six years at 24 participating preschools from June 2017 to July 2018. We determined the proportion of children immunised with influenza vaccine and PCV, and investigated socio-demographic factors associated with vaccine uptake using logistic regression models. Among 505 children, 77.5% were of Chinese ethnicity, and 53.1% were male. History of influenza vaccination was 27.5% of which 11.7% had been vaccinated within the past 12 months. In multivariable analyses, factors associated with influenza vaccine uptake were 'children living in landed property' (aOR = 2.25, 95% CI [1.07-4.67]) and 'history of hospitalisation due to cough' (aOR = 1.85, 95% CI [1.00-3.36]). Nearly three-quarters of participants (70.7% 95%CI: [66.6-74.5]) reported prior PCV vaccination. PCV uptake was higher for younger children. 'Higher parental education' (OR = 2.83, 95% CI [1.51,5.32]), 'household income' (OR = 1.26, 95% CI [1.08,1.48]) and 'smokers in household' (OR = 0.48, 95% CI [0.31,0.74]) were significantly associated with PCV uptake in univariable analyses. Only 'smokers in household' remained significantly associated with PCV uptake (aOR = 0.55, 95% CI [0.33,0.91]) in the adjusted model. Our results indicate that episodes of severe respiratory illness are a cue to influenza vaccination suggesting that doctors are more likely to recommend influenza vaccines to high-risk children. For PCV, our findings suggest overall greater awareness and education on the benefit of PCV vaccination is required.